System of accounting for energy efficiency and energy saving (Journal of Economic Research & Business Administration, 2016)
The article shows the main accounting system to improve energy efficiency and energy savings in abroad. The article analyzes the main indicators of energy efficiency system in different countries, such as Canada, USA, and Russia. The paper presents the experience of the European Union to establish energy accounting system: project ODYSSEE MURE. Proposed energy efficiency indicators applicable to the Republic of Kazakhstan: calculations the level of energy intensity of industrial production of primary energy, electric capacity of industrial production, the index of energy efficiency in industries, the energy intensity of agriculture, fuel economy of new passenger cars, the specific turnover of passengers of public transport per capita, energy intensity of municipal services ( water supply, sewerage and street lighting) per capita and the average specific energy consumption in homes.
Keywords: energy efficiency; energy intensity; energy policy; energy consumption; the decomposition method.